2012
DOI: 10.1038/onc.2012.498
|View full text |Cite
|
Sign up to set email alerts
|

RAD001 (everolimus) induces dose-dependent changes to cell cycle regulation and modifies the cell cycle response to vincristine

Abstract: More than 50% of adults and ~20% of children with pre-B acute lymphoblastic leukemia (ALL) relapse following treatment. Dismal outcomes for patients with relapsed or refractory disease mandate novel approaches to therapy. We have previously shown that the combination of the mTOR inhibitor RAD001 (everolimus) and the chemotherapeutic agent vincristine increases the survival of non-obese diabetic/severe combined immuno-deficient (NOD/SCID) mice bearing human ALL xenografts. We have also shown that 16 μM RAD001 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Inhibitors of mTOR have shown promise in preclinical models of ALL through the direct inhibition of tumor cell growth and also by reversal of glucocorticoid resistance . mTOR inhibitors have also demonstrated in vitro synergy in combination with a number of other chemotherapeutic agents, including dexamethasone, doxorubicin, l ‐asparaginase, methotrexate, and etoposide …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitors of mTOR have shown promise in preclinical models of ALL through the direct inhibition of tumor cell growth and also by reversal of glucocorticoid resistance . mTOR inhibitors have also demonstrated in vitro synergy in combination with a number of other chemotherapeutic agents, including dexamethasone, doxorubicin, l ‐asparaginase, methotrexate, and etoposide …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] mTOR inhibitors have also demonstrated in vitro synergy in combination with a number of other chemotherapeutic agents, including dexamethasone, doxorubicin, L-asparaginase, methotrexate, and etoposide. [13][14][15][16] Everolimus (Afinitor R ; Novartis), an oral mTOR inhibitor that does not require therapeutic monitoring, is approved for use in adults for a variety of indications including the treatment of breast cancer and pancreatic neuroendocrine tumors, and as an immunosuppressive agent in solid organ transplantation. In a phase I/II trial of everolimus in adults with refractory hematologic malignancies, no dose-limiting toxicities were identified at the two dose levels (DLs) tested (5 mg daily and 10 mg daily continuously).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding mTOR inhibition, RAD001 has been widely investigated for its role in suppressing tumoral cell growth . This inhibitor shows a more selective activity for the mTORC1 complex, and it is crucial in inducing caspase‐independent and ‐dependent cell death . In a phase I study enrolling children and adolescents with ALL experiencing a first marrow relapse, RAD001 was tested with the natural alkaloid Vincristine and the GC Prednisone or Doxorubicin in subjects with bone marrow relapse occurring >18 months after first CR.…”
Section: Targeted Therapymentioning
confidence: 99%
“…Also RAD001 has proven its efficacy, especially in models of Ph − pediatric B‐ALL. Importantly, RAD001 synergized with conventional chemotherapy (e.g., vincristine) or novel agents (e.g., bortezomib) both in vitro and in vivo, with increased caspase‐dependent, but p53‐independent, cell killing (Saunders, Cisterne, Weiss, Bradstock, & Bendall, ; Saunders et al, ). However, it has also been shown that RAD001 induces other types of cell death, including autophagy (Crazzolara, Bradstock, & Bendall, ) and caspase‐independent paraptosis (Baraz et al, ).…”
Section: Pi3k Inhibitorsmentioning
confidence: 99%